A piezo stack energy harvester with frequency up-conversion for rail track vibration. (1st October 2022) - Shan, Guansong; Zhu, Meiling
Highlights: The frequency spectrum of real track vibration is investigated. Frequency up-conversion method is used to up-convert the low-frequency vibration. A piezo stack energy harvester for track vibration is designed, modelled and tested. Stress of the mechanical transformer is analysed to ensure its reliability. An average power of 43 mW is obtained actuated at 18 Hz and 0.7 g rms acceleration. Abstract: To enable predictive and preventive maintenance in rail transportation systems, energy harvesting is a promising powering method. Piezoelectric energy harvesters have great powering potential, but so far the power harvested by piezoelectric railway generators is low. To explore the capability, this work presents a piezo stack energy harvester with frequency up-conversion method consisting of both the inertial mass system and the piezo stack transducer system from rail track vibration energy harvesting. The frequency up-conversion method uses the impact between the inertial mass system and the piezo stack transducer system to enable the piezoelectric transducer to operate at the transient resonant frequency response in spite that the input vibration frequency is much lower than the transducer one to achieve high-power generation. A theoretical model considering the impact between the two systems is established to describe the motion of the energy harvester. Numerical simulation and finite element analysis are conducted to model the proposed energy harvester and compared with experimental results to validate the proposed method. The time-dependent reactions, the frequency response characteristics, and the influence factors on output such as impedance, initial interval, acceleration, signal waveform are studied to evaluate the energy harvesting performance. In the experiments, the proposed energy harvester outputs a maximum power of 495.74 mW and an average power of 43.58 mW at an input rms acceleration of 0.7 g applied at 18 Hz with an optimum load impedance of 150 Ω, exhibiting good performance in comparison with the state-of-the-art piezoelectric energy harvesters applied on the rail track.